“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Bird guilds exhibit varied responses to floodplain forest restoration in the Colorado River delta, Mexico - Eduardo González-Sargas; Timothy D. Meehan; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Christopher Dodge; Martha Gómez-Sapiens; Pamela L. Nagler; Patrick B. Shafroth (Journal of Arid Environments, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Corrigendum to “Avian communities respond to plant and landscape composition in actively revegetated floodplains of the Colorado River delta in Mexico” [Ecological Engineering 205 (2024) 107266]. - Eduardo González-Sargas; Martha Gómez-Sapiens; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Alejandra Calvo-Fonseca; Joanna Grand; Timothy D. Meehan; Chris Dodge; Pamela L. Nagler; Carlos Restrepo-Giraldo; Carlos Nieblas; Angela Meléndez; et al. (Ecological Engineering, 2025)

Bird community response to one decade of riparian restoration along the Colorado River delta in Mexico - Eduardo González-Sargas; Timothy D. Meehan; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Alejandra Calvo-Fonseca; Christopher Dodge; Martha Gómez-Sapiens; Patrick B. Shafroth (Ecological Engineering, 2024)

Avian communities respond to plant and landscape composition in actively revegetated floodplains of the Colorado River delta in Mexico - Eduardo González-Sargas; Martha Gómez-Sapiens; Osvel Hinojosa-Huerta; Stefanny Villagomez-Palma; Alejandra Calvo-Fonseca; Joanna Grand; Timothy D. Meehan; Chris Dodge; Pamela L. Nagler; Carlos Restrepo-Giraldo; Carlos Nieblas; Angela Meléndez; et al. (Ecological Engineering, 2024)

Strategic restoration planning for land birds in the Colorado River Delta, Mexico - Joanna Grand; Timothy D. Meehan; William V. DeLuca; Julia Morton; Jennifer Pitt; Alejandra Calvo-Fonseca; Chris Dodge; Martha Gómez-Sapiens; Eduardo González-Sargas; Osvel Hinojosa-Huerta; Pamela Nagler; Carlos Restrepo-Giraldo; et al. (Journal of Environmental Management, 2024)

Opposing global change drivers counterbalance trends in breeding North American monarch butterflies - Michael S. Crossley; Timothy D. Meehan; Matthew D. Moran; Jeffrey Glassberg; William E. Snyder; Andrew K. Davis (Global Change Biology, 2022)
Many insects are in clear decline, with monarch butterflies ( Danaus plexippus ) drawing particular attention as a flagship species. It is well documented that, among migratory populations, numbers of overwintering monarchs have been falling across several decades, but trends among breeding monarchs are less clear. Here, we compile >135,000 monarch observations between 1993 and 2018 from the North American Butterfly Association's annual butterfly count to examine spatiotemporal patterns and potential drivers of adult monarch relative abundance trends across the entire breeding range in eastern and western North America. While the data revealed declines at some sites, particularly the US Northeast and parts of the Midwest, numbers in other areas, notably the US Southeast and Northwest, were unchanged or increasing, yielding a slightly positive overall trend across the species range. Negative impacts of agricultural glyphosate use appeared to be counterbalanced by positive effects of annual temperature, particularly in the US Midwest. Overall, our results suggest that population growth in summer is compensating for losses during the winter and that changing environmental variables have offsetting effects on mortality and/or reproduction. We suggest that density‐dependent reproductive compensation when lower numbers arrive each spring is currently able to maintain relatively stable breeding monarch numbers. However, we caution against complacency since accelerating climate change may bring growing threats. In addition, increases of summer monarchs in some regions, especially in California and in the south, may reflect replacement of migratory with resident populations. Nonetheless, it is perhaps reassuring that ubiquitous downward trends in summer monarch abundance are not evident.

Unraveling a century of global change impacts on winter bird distributions in the eastern United States - Sarah P. Saunders; Timothy D. Meehan; Nicole L. Michel; Brooke L. Bateman; William DeLuca; Jill L. Deppe; Joanna Grand; Geoffrey S. LeBaron; Lotem Taylor; Henrik Westerkam; Joanna X. Wu; Chad B. Wilsey (Global Change Biology, 2022)
One of the most pressing questions in ecology and conservation centers on disentangling the relative impacts of concurrent global change drivers, climate and land‐use/land‐cover (LULC), on biodiversity. Yet studies that evaluate the effects of both drivers on species’ winter distributions remain scarce, hampering our ability to develop full‐annual‐cycle conservation strategies. Additionally, understanding how groups of species differentially respond to climate versus LULC change is vital for efforts to enhance bird community resilience to future environmental change. We analyzed long‐term changes in winter occurrence of 89 species across nine bird groups over a 90‐year period within the eastern United States using Audubon Christmas Bird Count (CBC) data. We estimated variation in occurrence probability of each group as a function of spatial and temporal variation in winter climate (minimum temperature, cumulative precipitation) and LULC (proportion of group‐specific and anthropogenic habitats within CBC circle). We reveal that spatial variation in bird occurrence probability was consistently explained by climate across all nine species groups. Conversely, LULC change explained more than twice the temporal variation (i.e., decadal changes) in bird occurrence probability than climate change on average across groups. This pattern was largely driven by habitat‐constrained species (e.g., grassland birds, waterbirds), whereas decadal changes in occurrence probabilities of habitat‐unconstrained species (e.g., forest passerines, mixed habitat birds) were equally explained by both climate and LULC changes over the last century. We conclude that climate has generally governed the winter occurrence of avifauna in space and time, while LULC change has played a pivotal role in driving distributional dynamics of species with limited and declining habitat availability. Effective land management will be critical for improving species’ resilience to climate change, especially during a season of relative resource scarcity and critical energetic trade‐offs.

Effects of stewardship on protected area effectiveness for coastal birds - Nicole L. Michel; Sarah P. Saunders; Timothy D. Meehan; Chad B. Wilsey (Conservation Biology, 2021)
Evaluation of protected area effectiveness is critical for conservation of biodiversity. Protected areas that prioritize biodiversity conservation are, optimally, located and managed in ways that support relatively large and stable or increasing wildlife populations. Yet evaluating conservation efficacy remains a challenging endeavor. We used an extensive community science data set, eBird, to evaluate the efficacy of protected areas for birds across the Gulf of Mexico and Atlantic coasts of the United States. We modeled trends (2007–2018) for 12 vulnerable waterbirds that use coastal areas during breeding or wintering. We compared two types of protected areas—sites where conservation organizations implemented active stewardship or management or both to reduce human disturbance (hereafter stewardship sites) and local, state, federal, and private protected areas managed to maintain natural land cover (hereafter protected areas)—as well as unprotected areas. We evaluated differences in trends between stewardship, protected, and unprotected areas across the Gulf and Atlantic coasts as a whole. Similar to a background sample, stewardship was known to occur at stewardship sites, but unknown at protected and unprotected areas. Four of 12 target species—Black Skimmer ( Rynchops niger ), Brown Pelican ( Pelecanus occidentalis ), Least Tern ( Sternula antillarum ), and Piping Plover ( Charadrius melodus )—had more positive trends (two to 34 times greater) at stewardship sites than protected areas. Furthermore, five target species showed more positive trends at sites with stewardship programs than unprotected sites during at least one season, whereas seven species showed more positive trends at protected than unprotected areas. No species had more negative trends at stewardship sites than unprotected areas, and two species had more negative trends at protected than unprotected areas. Anthropogenic disturbance is a serious threat to coastal birds, and our findings demonstrate that stewardship to reduce its negative impacts helps ensure conservation of vulnerable waterbirds.

Top-down cortical interactions in visuospatial attention - Timothy P. Meehan; Steven L. Bressler; Wei Tang; Serguei V. Astafiev; Chad M. Sylvester; Gordon L. Shulman; Maurizio Corbetta (Brain Structure and Function, 2017)

Effects of Elevated Atmospheric Carbon Dioxide and Tropospheric Ozone on Phytochemical Composition of Trembling Aspen ( Populus tremuloides ) and Paper Birch ( Betula papyrifera ) - John J. Couture; Timothy D. Meehan; Kennedy F. Rubert-Nason; Richard L. Lindroth (Journal of Chemical Ecology, 2017)

Butterfly community structure and landscape composition in agricultural landscapes of the central United States - Timothy D. Meehan; Jeffrey Glassberg; Claudio Gratton (Journal of Insect Conservation, 2013)

Atmospheric change alters foliar quality of host trees and performance of two outbreak insect species - John J. Couture; Timothy D. Meehan; Richard L. Lindroth (Oecologia, 2012)

Initial Response of Soil Carbon and Nitrogen to Harvest Intensity and Competing Vegetation Control in Douglas-Fir ( Pseudotsuga menziesii ) Plantations of the Pacific Northwest - Robert A. Slesak; Stephen H. Schoenholtz; Timothy B. Harrington; Nathan A. Meehan (Forest Science, 2011)
We assessed the effect of harvest type (bole-only or whole-tree) and vegetation control treatments (initial or annual application of herbicide) on soil C and N at two contrasting sites in the Pacific Northwest. Pretreatment (2003) and posttreatment (2005) soil samples were collected by depth to 60 cm, and a stratified sampling approach based on four surface conditions was used for posttreatment sampling in surface soils. Surface condition had a significant effect on soil C and N concentrations, generally decreasing with decreasing amounts of logging debris and increasing soil disturbance. There was no difference between harvest treatments in the change in soil C and N content despite differences in surface condition coverage between harvest types, indicating estimates of C and N change determined from the stratification approach were imprecise. Soil C and N content tended to increase regardless of treatment, but increases were significant only in the bole-only harvest at one site and in the whole-tree harvest at the other site. Initial vegetation control caused significantly greater positive change in soil C and N than the annual vegetation control treatment, with effects limited to surface soil at one site and all sample depths at the other site. Much of these increases occurred in deeper (>20 cm) parts of the soil profile, indicating that deep soil sampling is necessary for assessment of harvest-related change in soil C and N.

Soil carbon and nitrogen mineralization following deposition of insect frass and greenfall from forests under elevated CO2 and O3 - Michael Hillstrom; Timothy D. Meehan; Kristine Kelly; Richard L. Lindroth (Plant and Soil, 2010)

Cylinders vs. Spheres: Biofluid Shear Thinning in Driven Nanoparticle Transport - Jeremy A. Cribb; Timothy D. Meehan; Sheel M. Shah; Kwan Skinner; Richard Superfine (Annals of Biomedical Engineering, 2010)

Mass invariance of population nitrogen flux by terrestrial mammalian herbivores: an extension of the energetic equivalence rule - Christopher W. Habeck; Timothy D. Meehan (Ecology Letters, 2008)
According to the energetic equivalence rule, energy use by a population is independent of average adult body mass. Energy use can be equated with carbon flux, and it has been suggested that population fluxes of other materials, such as nitrogen and phosphorus, might also be independent of body mass. We compiled data on individual nitrogen deposition rates (via faeces and urine) and average population densities of 26 species of mammalian herbivores to test the hypothesis of elemental equivalence for nitrogen. We found that the mass scaling of individual nitrogen flux was opposite to that of population density for the species in our dataset. By computing the product of individual nitrogen flux and average population density for each species in our dataset, we found that population‐level nitrogen flux was independent of species mass, averaging c. 3.22 g N ha −1 day −1 . Results from this analysis can be used to understand the influence of mammalian herbivore communities on nitrogen cycling in terrestrial ecosystems.

Modeling nitrogen flux by larval insect herbivores from a temperate hardwood forest - Timothy D. Meehan; Richard L. Lindroth (Oecologia, 2007)

Energetic determinants of abundance in winter landbird communities - Timothy D. Meehan; Walter Jetz; James H. Brown (Ecology Letters, 2004)
There is increasing evidence that individual energetics constrain macroecological patterns. Here we model total abundance within winter landbird communities as a function of (1) energy supply, as measured by ecosystem net primary productivity, and (2) energy use of individuals, as influenced by body mass and ambient temperature. Using data from the North American Christmas Bird Count, we find that total abundance increases with productivity to the 0.61 power, and decreases with body mass and environmental temperature as predicted by metabolic theory when individuals are below their thermoneutral zone. We note a negative relationship between ambient temperature and average body mass, and suggest that this community‐level pattern, reminiscent of Bergmann's Rule, is related to a tendency for small species to be less‐abundant or absent from cold locations. Results from this study emphasize the importance of individual‐level metabolism for understanding large‐scale ecological patterns.

Estimating the latitudinal origins of migratory birds using hydrogen and sulfur stable isotopes in feathers: influence of marine prey base - Casey A. Lott; Timothy D. Meehan; Julie A. Heath (Oecologia, 2003)